2012
DOI: 10.1080/1034912x.2012.697743
|View full text |Cite
|
Sign up to set email alerts
|

Stories about Physical Education from Young People with Disabilities

Abstract: This article focuses on young people with disabilities and mainstream physical education in England. Within this context there have been unprecedented levels of funding and resources directed towards physical education in order to support more inclusive physical education experiences for all young people, including those with disabilities. Physical education holds a unique place within the school curriculum; it is a subject area where the physicality of students is publicly exposed to others (including teacher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 32 publications
0
43
0
1
Order By: Relevance
“…La investigación narrativa que se ocupa de las voces de colectivos discriminados ha seguido desarrollándose posteriormente (BERG SVENDBY;DOWLING, 2012;FITZGERALD;STRIDE, 2012;GROVES;LAWS, 2003;MAIVORSDOTTER;LUNDVALL, 2009;RICH, 2004;SYKES;GOLDSTEIN, 2004;WRENCH;GARRETT, 2012). Pero también se observa un interés creciente por estudios auto-narrativos que se ocupan de experiencias subjetivas diversas y de corporalidades individuales.…”
Section: La Investigación Narrativa: Un Breve Recorridounclassified
“…La investigación narrativa que se ocupa de las voces de colectivos discriminados ha seguido desarrollándose posteriormente (BERG SVENDBY;DOWLING, 2012;FITZGERALD;STRIDE, 2012;GROVES;LAWS, 2003;MAIVORSDOTTER;LUNDVALL, 2009;RICH, 2004;SYKES;GOLDSTEIN, 2004;WRENCH;GARRETT, 2012). Pero también se observa un interés creciente por estudios auto-narrativos que se ocupan de experiencias subjetivas diversas y de corporalidades individuales.…”
Section: La Investigación Narrativa: Un Breve Recorridounclassified
“…Disabled students tell about classmates who do not accept them, call them names, stare at them or make fun of their capacities during the physical activity. They have experiences of not being chosen when teams are formed, and of classmates that do not pass them the ball when playing team games (Brittain, 2004;Fitzgerald, 2005;Fitzgerald & Stride, 2012;Lauruschkus et al, 2015). These negative experiences may give rise to feelings of difference and inferiority (Gaskin et al, 2012), thus affecting other parts of the disabled students' life, and can lead to avoidance of physical activity outside school and as an adult (Brittain, 2004;Fitzgerald & Stride, 2012;Gaskin et al, 2012).…”
Section: (Dis)ability and Pementioning
confidence: 99%
“…Previous studies about the situation for young disabled people at school or in physical activity in general (Asbjørnslett & Hemmingsson, 2008;Barron, 1996;Bredahl, 2013;Gaskin, Andersen, & Morris, 2012;Lauruschkus, Hallström, & Nordmark, 2015;Taub & Greer, 2000) or in PE per se (Fitzgerald, 2005;Fitzgerald & Stride, 2012;van Amsterdam, Knoppers, & Jongmans, 2015) have shown that disabled students often feel excluded, singled out and picked on during lessons in PE. The 'visibility' of bodies and abilities during the lessons and in the dressing and shower rooms, with the ensuing experience of vulnerability, is underlined (Barron, 1995;Bredahl, 2013;Fitzgerald & Stride, 2012).…”
Section: (Dis)ability and Pementioning
confidence: 99%
See 2 more Smart Citations